Curcumin induces autophagic cell death in Spodoptera frugiperda cells - Veeran, Sethuraman; Shu, Benshui; Cui, Gaofeng; Fu, Shengjiao; Zhong, Guohua (Pesticide biochemistry and physiology, 2017)
The increasing interest in the role of autophagy (type II cell death) in the regulation of insect toxicology has propelled study of investigating autophagic cell death pathways. Turmeric, the rhizome of the herb Curcuma longa (Mañjaḷ in Tamil, India and Jiānghuáng in Chinese) have been traditionally used for the pest control either alone or combination with other botanical pesticides. However, the mechanisms by which Curcuma longa or curcumin exerts cytotoxicity in pests are not well understood. In this study, we investigated the potency of Curcuma longa (curcumin) as a natural pesticide employing Sf9 insect line. Autophagy induction effect of curcumin on Spodoptera frugiperda (Sf9) cells was investigated using various techniques including cell proliferation assay, morphology analysis with inverted phase contrast microscope and Transmission Electron Microscope (TEM) analysis. Autophagy was evaluated using the fluorescent dye monodansylcadaverine (MDC). Cell death measurement was examined using 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) within the concentrations of 5–15μg/mL. Curcumin inhibited the growth of the Sf9 cells and induced autophagic cell death in a time and dose dependent manner. Staining the cells with MDC showed the presence of autophagic vacuoles while increased in a dose and time dependent manner. At the ultrastructural level transmission electron microscopy, cells revealed massive autophagy vacuole accumulation and absence of chromatin condensation. Protein expression levels of ATG8-I and ATG8-II, well-established markers of autophagy related protein were elevated in a time dependent manner after curcumin treatment. The present study proves that curcumin induces autophagic cell death in Sf9 insect cell line and this is the first report of cytotoxic effect of curcumin in insect cells and that will be utilized as natural pesticides in future. [Display omitted] •Curcumin inhibited the growth of Sf9 cells.•Curcumin induced autophagic cell death in Sf9 insect cell line.•SfAtg8/LC3 level increased in a time dependent manner upon curcumin treated Sf9 cells.